2022
DOI: 10.1155/2022/6539917
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors and Treatments of Suprachoroidal Hemorrhage

Abstract: Suprachoroidal hemorrhage (SCH) is a rare but serious sight-threatening complication of inner eye surgery. Despite continuous advances in treatment, visual prognosis remains poor. The disease has a more typical clinical presentation, the etiology and pathogenesis are not well defined, and intraoperative ocular and systemic factors may induce fulminant SCH. To investigate risk factors and treatments of SCH-associated intraocular surgeries, summarize diagnosis, characteristics, management, and prevention of SCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 19 publications
(100 reference statements)
1
19
0
Order By: Relevance
“…This was also true when comparing ischemic optic neuropathy versus optic neuritis in patients that developed optic neuropathy after COVID-19 vaccination [61]. Ocular hemorrhagic events were also specifically linked to advanced age [66], which is the case in our population. Older patients (74.2 ± 9.11) had a higher incidence of hemorrhagic vascular complications.…”
Section: Discussionsupporting
confidence: 59%
“…This was also true when comparing ischemic optic neuropathy versus optic neuritis in patients that developed optic neuropathy after COVID-19 vaccination [61]. Ocular hemorrhagic events were also specifically linked to advanced age [66], which is the case in our population. Older patients (74.2 ± 9.11) had a higher incidence of hemorrhagic vascular complications.…”
Section: Discussionsupporting
confidence: 59%
“…As cataract surgery is widely accepted as an elective procedure, several authors have suggested that adopting certain preventive measures that may be performed before, during, or after surgery could avoid the occurrence of SCH [ 1 , 5 , 13 ].…”
Section: Managementmentioning
confidence: 99%
“…First of all, patients recommended for cataract surgery, especially when considered to be high-risk cases, should be thoroughly evaluated in advance, paying particular attention to both systemic and ocular risk factors for SCH [ 1 , 5 , 13 ]. In this regard, a comprehensive examination should be undertaken, looking for cardiovascular disease, liver failure, coagulation abnormalities, and the use of cardiovascular medication [ 5 ].…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations